Do global uncertainties and financial distress impact Sukuk issuance? - Baykut, Ender (Universitas Islam Indonesia, 2025)
Purpose ― This paper examines the impact of major uncertainty indices and global uncertainty on the volume of Sukuk issuance in Türkiye. Method — The NARDL method is applied to determine the short- and long-term relationships between Türkiye's sukuk issuance and global uncertainty and financial stress indices, capturing both symmetric and asymmetric dimensions.Findings — Although a symmetric relationship exists between Global Economic Policy Uncertainty (GEPU) and Sukuk issuance, the Financial Stress Index (FSI) has no long-term impact on Sukuk issuance. During periods of global uncertainty, sukuk issuances increase, whereas in conditions of less uncertainty, they fall. There is an inverse relationship between Geopolitical Risk (GPR) and Sukuk issuance. Since all factors affect sukuk issuance in the short run, GEPU has the highest impact. Decreases in the GEPU index positively affect sukuk securities and increase their issuance volumes. Therefore, GPR and GEPU indices have asymmetric effects on sukuk issuances in the short and long term.Implication — Evidence suggests that sukuk is more resilient to crises than its conventional equivalents. Sukuks are strategically crucial for portfolios and provide sufficient assurance to reduce risk.Originality — No study has assessed how global financial distress and uncertainty influence Türkiye's sukuk issuance. This study differs from previous studies by focusing on sukuk issuance volumes rather than sukuk yields.